Mesenchymal stromal cell-derived extracellular vesicles as nanotherapeutics for concanavalin a-induced hepatitis: modulating the gut‒liver axis - Fan Yang; Beibei Ni; Xiaoqi Liang; Yizhan He; Chao Yuan; Jiajie Chu; Yiju Huang; Hongyu Zhong; Li Yang; Jianxi Lu; Yan Xu; Qi Zhang; et al. (Stem Cell Research & Therapy)
Abstract Background As cell-free nanotherapeutics, extracellular vesicles derived from mesenchymal stem cells (MSC-EVs) have shown potential therapeutic action against liver diseases. However, their effects on autoimmune hepatitis (AIH) are not yet well understood. Methods and results In this study, we utilized a well-established concanavalin A (Con A)-induced fulminant hepatitis mouse model to investigate the effects of MSC-EVs on AIH. We found that MSC-EVs provide significant protection against Con A-induced hepatitis in C57BL/6 male mice, with their effectiveness being critically dependent on the gut microbiota. MSC-EVs modulate the composition of the gut microbiota, particularly by increasing the abundance of norank_f__Muribaculaceae, and impact liver metabolic profiles, leading to significant amelioration of liver injury. The identification of Acetyl-DL-Valine as a protective metabolite underscores the therapeutic potential of targeting gut‒liver axis interactions in liver diseases. Conclusion Overall, our data demonstrate that MSC-EVs exhibit nanotherapeutic potential in Con A-induced hepatitis and provide new insights into the treatment of autoimmune hepatitis. Graphical Abstract